Transformation of molecular CO2-III in low-density carbon to extended CO2-V in porous diamond at high pressures and temperatures. (12th July 2018) - Kim, Minseob; Ryu, Young Jay; Lim, Jinhyuk; Yoo, Choong-Shik
Abstract: The ability to modify chemical bonding in dense heterogeneous solid mixtures by applying high pressure and temperature opens new opportunities to develop a greater number of novel materials with controlled structure, stability and exceptional physical properties. Here, we present the transformation of highly strained CO2 -III ( Cmca ) filled in porous low-density carbons (LDC) to extended CO2 -V ( I- 42 d ) encapsulated in porous diamond ( Fd- 3 m ) at high pressures and temperatures. The x-ray diffraction data indicates the density of porous diamond is about 5%–8% lower than that of bulk diamond and undergoes the structural distortion to monoclinic diamond ( C 2 /m or M-carbon) upon pressure unloading. This result, therefore, demonstrates a feasibility to use porous LDC as nm-scale reactors to synthesize and store carbon dioxide and other high energy density extended solids.